Sequence analysis, expression, and paratope characterization of a single-chain Fv fragment for the eukaryote ribosomal P proteins - Lopez Bergami, Pablo Roberto (2003)
The variable genes of monoclonal antibody (mAb) B10, specific for the C-terminal region of the eukaryotic ribosomal P protein, have been cloned as a single-chain Fv fragment (scFv) and expressed in Escherichia coli. The primary sequence of the variable regions of the B10 antibody, together with a detailed characterization of the reactive residues of the antigen, allowed the construction of a model of the paratope–epitope interaction, giving a first insight into the binding mechanisms of anti-P autoantibodies to their target peptides. The mAb and scFv could be useful for extensive P protein detection since both recognize the highly conserved motif DDxGF.